EVALUASI DIGITAL MARKETING BERBASIS INSTAGRAM DALAM PENINGKATAN KEPUTUSAN MELANJUTKAN PENDIDIKAN DI SMK PGRI 2 KARAWANG - Paujiah, Popon; Muhamad Taufik Bintang Kejora; Nur Rochimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate Instagram-based digital marketing in improving students' decision to continue their education at SMK PGRI 2 Karawang. The research employed a qualitative approach with an evaluative case study method. The evaluation model used was CIPP, consisting of context, input, process, and product. Data were collected through observation, interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The findings show that Instagram is relevant to the needs of prospective students who actively seek school information through social media. In terms of input, the school has assigned managers, supporting devices, and various content formats such as photos, videos, digital posters, stories, and reels. In the process aspect, Instagram is used to deliver information about school activities, student achievements, facilities, and student admission information while building interaction with prospective students. In the product aspect, Instagram contributes to increasing school awareness, interest, confidence, and students' decisions to continue their education. However, posting consistency and content variation still need to be improved so that digital marketing can run more optimally.